Análise comparativa da casualidade sísmica do Algarve - Estêvão, João M. C. (2009)
In this paper we compared the seismic hazard of Algarve obtained with two different models: a point-source model (proposed by McGuire) and a fault-rupture model (proposed by Der Kiureghian and Ang).